A Question of Identity: Exploring Cultural Assimilation Through Writing Fiction - Alda Sigmundsdóttir 1962- (2014)
This creative writing assignment is my submission for the final BA project in English at the School of Humanities at the University of Iceland. The assignment consists of Part I of my novel The Simple Life, which is approximately 30,000 words, followed by an exposition on the writing process, which is about 5,500 words. The Simple Life is a literary novel focusing on a young girl, Anna, and her move from Iceland to Canada in the 1970s. In Canada, Anna’s mother Ella hopes to find a simpler life than the one she has been living. However, her attempt is misguided, as she fails to recognise that one cannot escape the ghost of the past by simply relocating to a new country. The story is told through the point of view of Anna, who struggles to cope with the demands of a new culture and her own mother’s betrayal of her, while simultaneously watching her mother decline into her own private hell, with catastrophic results. The exposition traces the process of writing the book, and discusses what I hoped to achieve in terms of characterisation, plot, setting and theme. Through this work I try to explore the question of identity, in particular cultural identity, and the meaning of emotional legacy when it comes to creating a new life for oneself. Unfortunately due to the length of the novel I was only able to submit Part I, and not the whole work as I would have preferred. I nevertheless hope that it is able to provide a clear indication of what I have learned, and of what I am capable as a writer.